Status Of Broiler Production In Kerala With Special Reference To Trichur - Aboobacker M (Department of Poultry Science, College of Veterinary, 1988)
A survey was undertaken to assess the present status of broiler farming in Thrissur, a major broiler producing district in Kerala. Thirtytwo farms were selected for the survey based on holding strength and frequency of intake.